Facial Expressions of Basic Emotions in Japanese Laypeople - Sato, Wataru; Hyniewska, Sylwia; Minemoto, Kazusa; Yoshikawa, Sakiko (Frontiers in Psychology, 2019)
Facial expressions that show emotion play an important role in human social interactions. In previous theoretical studies, researchers have suggested that there are universal, prototypical facial expressions specific to basic emotions. However, the results of some empirical studies that tested the production of emotional facial expressions based on particular scenarios only partially supported the theoretical predictions. In addition, all of the previous studies were conducted in Western cultures. We investigated Japanese laypeople (n = 65) to provide further empirical evidence regarding the production of emotional facial expressions. The participants produced facial expressions for six basic emotions (anger, disgust, fear, happiness, sadness, and surprise) in specific scenarios. Under the baseline condition, the participants imitated photographs of prototypical facial expressions. The produced facial expressions were automatically coded using FaceReader in terms of the intensities of emotions and facial action units. In contrast to the photograph condition, where all target emotions were shown clearly, the scenario condition elicited the target emotions clearly only for happy and surprised expressions. The photograph and scenario conditions yielded different profiles for the intensities of emotions and facial action units associated with all of the facial expressions tested. These results provide partial support for the theory of universal, prototypical facial expressions for basic emotions but suggest the possibility that the theory may need to be modified based on empirical evidence.